Religion and society in sub-Saharan Africa and Southern Asia - Rakodi, Carole (Routledge research in religion and development, 2019)
The religion-society nexus: introduction -- The entanglements of religion in everyday life -- Towards a framework for analysing the links between religion and society -- Religious beliefs and their implications for people's lives -- Religious beliefs: sources, interpretations -- Religious beliefs and people's lives: death, destiny and wellbeing -- Religious practices -- The role of ritual -- Discipline, joy and learning -- Values, ethics and everyday lives -- Freedom, rights and justice -- Wellbeing, poverty, and inequality -- Gender equality, sexuality and the family.